English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-20 07:47:13 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

(5/4) - (5/9) = (x/12)

Multiply everything by 36

45 - 20 = 3x
3x = 25
x = 8 1/3

2006-12-20 11:37:25 · answer #1 · answered by Sherman81 6 · 1 0

First: get rid of fractions > take the denominators and multiply them by everything:

4(9)(12)(5/4) - 4(9)(12)(5/9) = 4(9)(12)(x/12)

Second: cross cancel "like" terms:

9(12)(5) - 4(12)(5) = 4(9)(x)
540 - 240 = 36x
300 = 36x

Third: solve for "x" by keeping it on one side: divide both sides by 36

300/36 = 36x/36
25/3 = x; x = 25/3

2006-12-20 14:59:40 · answer #2 · answered by ♪♥Annie♥♪ 6 · 0 0

5/4 - 5/9 = x/12
5/4 *9 - 5/9 * 4 = x/12
45/36 - 20/36 = x/12
25/36 = x/12
25/36 * 36 = x/12 * 36
3x = 25
x = 25/3

2006-12-20 11:08:16 · answer #3 · answered by Roamer 2 · 1 0

one million. -8/63b = -4/9 sixty 3/one million (-8/63b) = (-4/9) sixty 3/one million -8b = -28 -8b/-8 = -28/-8 b=3.5 2. i don't remember the thank you to do absolute values. Sorry. 3. p + q - (0.7) = ? the place p = 0.seventy 5 and q=-one million.6 0.seventy 5 + -one million.6 - (0.7) =? -0.eighty 5 - (0.7) =? = -one million.fifty 5 4. 3/5 = 9/10b 5/one million (3/5) = (9/10b) 5/one million 3 = 9/2b (3) 2/one million = (9/2b) 2/one million 6 = 9b 6/9 = (9b) / 9 6/9 = b 2/3 = b 5. 3(x + 12)/5 = x + 2 *use the distributive ingredients (3x + 36)/5 = x + 2 5/one million {(3x + 36)/5} = (x + 2) 5/one million 3x + 36 = 5x + 10 (3x + 36) - 3x = (5x +10) - 3x 36 = 2x +10 (36) - 10 = (2x + 10) - 10 26 = 2x (26) / 2 = (2x) / 2 13 = x 6. 6 (y-2) + 5 = -13 *You used the distributive ingredients wisely 6y - 12 + 5 = -13 6y - 7 = -13 (6y - 7) + 7 = -13 + 7 6y = -6 (6y) / 6 = (-6) / 6 y = -one million 7. 5(x-3)/4 = x+one million *Use distributive ingredients (5x-15)/4 = x+one million 4/one million {(5x-15)/4} = (x+one million) 4/one million 5x-15 = 4x+4 (5x-15) +15 = (4x+4) +15 5x = 4x+19 (5x) - 4x = (4x+19) - 4x x = 19

2016-12-30 17:13:10 · answer #4 · answered by ? 3 · 0 0

You need to find the least common multiple for the left side of the equation so that you can combine terms. The least common multiple is 36, so the problem can be re-stated as:

45/36 - 20/36 = x/12

25/36 = x/12

for x/12 to equal 25/36, you re-state it with least common multiple as follows:

25/36 = 3x/36

so 3x = 25
so x = 25/3 = 8 1/3

2006-12-20 09:07:21 · answer #5 · answered by bruinfan 2 · 1 0

5/4 - 5/9 = x/12
45/36 - 20/36 = 3x/36
25/36 = 3x/36
x = 25/3
QED

2006-12-20 09:53:08 · answer #6 · answered by CSUFGrad2006 5 · 1 0

fedest.com, questions and answers